PENGARUH EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP HEMATOKRIT MENCIT (Mus musculus L. Swiss Webster) BETINA - Serfitria, Sherly; Sumarmin, Ramadhan; Widiana, Rina (Pendidikan Biologi, 2014)
Â Mangosteen (Garcinia mangostana L.) is a traditional remedy containing xanthone compounds. Xanthones are the active compounds in the mangosteen rind that is as an immunomodulator, so that it can stabilize erythrocytes in the body and can normalize or optimize the work of the immune system so that the components in the blood stable. Xanthone compounds play a role in accelerating the formation of red blood cells in the blood. This study aims to determine the effect of extracts of mangosteen rind (Garcinia mangostana L.) against Hematocrit mice (Mus musculus L. Swiss Webster) females. This study is an experimental study using animal mice (Mus musculus L. Swiss Webster) Females as 4 treatments and 6 replications. The treatments were mangosteen rind extract with dose variations, namely K is the control treatment, without being given the mangosteen peel extract, treatment of P1, P2 and P3 are given treatment mangosteen extract orally for 26 days with doses of 0.2, 0.4 and 0.6 mg / head / day. Parameters measured were the percentage of hematocrit values. Data is tested with parametric ANOVA (Analysis of Variance). The results showed that the extract of mangosteen peel (Garcinia mangostana L.) had no effect on hematocrit values. The percentage of hematocrit value in P1 is 44.98 %, ie 46.30 % P2, P3 are47.89 % and 44.07 % of control. It can be concluded that mangosteen peel extract fed orally for 26 days on a statistical test had no significant effect on hematocrit values but the result showed an increase.